Effect of Product Placement Belief on Brand Awareness - Limbu, Ashim Hang; Aryal, Mani Ram (Nepalese Journal of Business and Management Studies, 2022)
Previous research papers have established product placement as a practical marketing tool to raise awareness and shift attitudes. However, limited research has contributed to acceptance, perception, and belief of product placement and its effect on brand awareness. Even though the variables of this research have been employed before, product placement was only measured in real-time under the experimental research design, and brand awareness was neglected while measuring user behavior. This research paper has attempted to measure the belief of product placement and brand awareness amongst moviegoers. Due to the restrictions of COVID this research has selected a sample population of Instagram followers of FCube cinema situated in the Chabahil area. Here, product placement belief is an independent variable, and brand awareness is a dependent variable. Data collection was collected from 94 respondents representing the sample size. The research design embraced in the study consists of relational, and causal research designs. The results suggest that various belief segments affects the degree of brand awareness. The discussion concludes with managerial implications providing insights about the interface between the targeted audience’s beliefs regarding the commercialization of the movies and its effect on brand awareness helping brand managers and marketers to understand reliability of product marketing.